2022
DOI: 10.1186/s12890-022-01940-0
|View full text |Cite
|
Sign up to set email alerts
|

Salt-inducible kinase 2 (SIK2) inhibitor ARN-3236 attenuates bleomycin-induced pulmonary fibrosis in mice

Abstract: Background Pulmonary fibrosis is a fatal lung disease with complex pathogenesis and limited effective therapies. Salt-inducible kinase 2 (SIK2) is a kinase that phosphorylates CRTCs and regulates many physiological processes. However, the role of SIK2 on pulmonary fibrosis remains unclear, and whether SIK2 inhibitor can attenuate pulmonary fibrosis is unknown. Method We subjected human fetal lung fibroblasts (HFLs) to transforming growth factor-β1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is likely that MyD88 (a key intracellular adapter for TLR signaling) prevents pulmonary fibrosis by regulating NF-κB activation to attenuate RILI ( Table 1 ) [ 105 ]. The SIK2 (salt-inducible kinase-2) inhibitor ARN-3236 was recently reported to attenuate bleomycin-induced pulmonary fibrosis in mice [ 106 ]. This gives us new candidate targets for a more comprehensive search for appropriate therapeutic approaches.…”
Section: Therapy Strategy Of Ripf By Targeting Emtmentioning
confidence: 99%
“…It is likely that MyD88 (a key intracellular adapter for TLR signaling) prevents pulmonary fibrosis by regulating NF-κB activation to attenuate RILI ( Table 1 ) [ 105 ]. The SIK2 (salt-inducible kinase-2) inhibitor ARN-3236 was recently reported to attenuate bleomycin-induced pulmonary fibrosis in mice [ 106 ]. This gives us new candidate targets for a more comprehensive search for appropriate therapeutic approaches.…”
Section: Therapy Strategy Of Ripf By Targeting Emtmentioning
confidence: 99%
“…We show here that nintedanib inhibits SIK2 with similar potency to its known tyrosine kinase targets both in vitro and in cells. Supporting a role for SIK2, a recent study has shown that a compound developed as an SIK inhibitor, ARN-3236, is able to attenuate bleomycin-induced lung fibrosis ( 63 ). ARN-3236 has selectivity for SIK2 over SIK1 and SIK3 with in vitro IC 50 values reported as <1, 21.6, and 6.6 nM, respectively ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the anti-fibrosis of dasatinib depends on SIKs is unclear. A recently study showed that SIK2 expression and activity is increased in fibrotic lung tissues and activated fibroblasts ( Zou et al, 2022 ). A selective SIK2 inhibitor ARN-3236 restricts fibroblasts differentiation and ECM gene expression in human fetal lung fibroblasts and attenuates bleomycin-induced pulmonary fibrosis in mice ( Zou et al, 2022 ), supporting as pathological role for SIK2 in pulmonary fibrosis.…”
Section: Fibrosismentioning
confidence: 99%